2015
DOI: 10.21002/jaki.2015.05
|View full text |Cite
|
Sign up to set email alerts
|

Indikasi Penyalahgunaan Discretionary Fund Dalam Anggaran Pendapatan Dan Belanja Daerah Menjelang Pemilukada 2015

Abstract: This study aims to investigate the possibility of any indication of misuse of discretionary funds in the budget, and to obtain empirical evidence on the factors of budget capability and political motives that affect the proportion of these funds before the local election in 2015. The study was conducted in 143 districts/cities in Indonesia in 2015 which implement the local election simultaneously. The results using t-test showed that there was no different proportion of discretionary funds before and ahead of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
15
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 14 publications
5
15
1
2
Order By: Relevance
“…Meaning a local government with a high discretionary budget will create a chance for corruption resulting in higher financial losses. This result is consistent with past research from [18] [17], which showed that grant and social assistance budgets were discretionary funds that determined the magnitude of the budget and tended to be subjective [5] Table X shows the result of a Mann-Whitney test on the extent of corruption in non-discretionary budgets. The result shows that the Z value is not significant, having a p-value greater than 0.05.…”
Section: B Empirical Results and Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Meaning a local government with a high discretionary budget will create a chance for corruption resulting in higher financial losses. This result is consistent with past research from [18] [17], which showed that grant and social assistance budgets were discretionary funds that determined the magnitude of the budget and tended to be subjective [5] Table X shows the result of a Mann-Whitney test on the extent of corruption in non-discretionary budgets. The result shows that the Z value is not significant, having a p-value greater than 0.05.…”
Section: B Empirical Results and Discussionsupporting
confidence: 89%
“…Winoto and Falikhatun [4] stated that grants and social assistance budgets are discretionary funds whose budget determination tends to be subjective. Research conducted by Winoto and Falikhatun [17] found that the greater the fiscal space (local financial capacity) the greater the flexibility of its allocation to local expenditure, including grants and social expenditures. In addition, research of Ritonga and Alam [18] found indications of irregularities in APBD, especially in grant and social assistance budget prior to the election.…”
Section: B Hypothesis Development 1) Discretionary Budget Corruptiomentioning
confidence: 99%
“…Specific to the local governments in Indonesia, Ritonga and Alam (2010) find that the allocation of grant and social assistance expenditure in incumbent regions during the election year is higher than prior to the elections. As mentioned, evidence from the studies by Sjahrir et al (2013) and Winoto and Falikhatun (2015) find that discretionary funds spending is positive and significant nearing and during election time respectively. Taufiq and Purnomowati (2017) investigate the possibility of misuse of discretionary funds in local governments' budget by incumbents before election and find higher proportion of budget allocation on grant and social assistance expenditure related to incumbent regions during the local election in 2015.…”
Section: Literature Reviewmentioning
confidence: 85%
“…The local executive heads have been given many authorities including on fiscal policy, while there are some budget components that are at their discretion judgment. These budget namely "discretionary funds" could be intentionally utilized to impress the voters and enhance their re-election prospect later on (Sjahrir et al, 2013;Winoto and Falikhatun, 2015). Re-running candidates also tend to allocate the budget not based on reliable benchmarks but depend on their vested interests (Ritonga and Alam, 2010).…”
mentioning
confidence: 99%
“…Nevertheless, election is obviously a financial burden and conflict-prone issue. The use of the Local Revenue and Expenditure Budget (APBD) for personal interests is a common issue prior to the general elections (Winoto & Falikhatun, 2015). It is indicated by alleged budget irregularities and corruption carried out by regional heads approaching the election (Mietzner, 2011 as cited in Winoto & Falikhatun, 2015).…”
Section: Introductionmentioning
confidence: 99%